2016
DOI: 10.4028/www.scientific.net/kem.696.80
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Properties of Montmorillonite for their Cytocompatibility

Abstract: We modified the surface of organically modified montmorillonite (OMMT) with the carboxyl group using the silane coupling reaction and assessed its characteristics and cytocompatibility. Scanning electron microscope observations show that while the size and morphology of the obtained OMMT (OMMT-COOH) was unchanged, the surface of OMMT-COOH was coarser than that of OMMT. Fourier transform infrared spectra showed characteristic strong peaks at 1210 and 1630 cm−1, corresponding to the peaks of the carboxyl group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Gulati et al, reported that titania nanotubes indicated excellent molecule-load and release behavior when their internal structures were prepared [8]. We also investigated in the possibility of nano-porous silica nanoparticles for controlled drug-release system [9,10]. Based on the viewpoint of dental fields, many researchers has been interested in sustainably release materials of calsium and fluorine ions because the sustainable release of fluorine is expect to reduce the incidence of caries due to fluorapatite formation and remineralization [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Gulati et al, reported that titania nanotubes indicated excellent molecule-load and release behavior when their internal structures were prepared [8]. We also investigated in the possibility of nano-porous silica nanoparticles for controlled drug-release system [9,10]. Based on the viewpoint of dental fields, many researchers has been interested in sustainably release materials of calsium and fluorine ions because the sustainable release of fluorine is expect to reduce the incidence of caries due to fluorapatite formation and remineralization [11][12][13].…”
Section: Introductionmentioning
confidence: 99%